PROCESSING CRISPY ENBAL MAS NGUR BASED ORGANOLEPTIK LOCAL FOOD IN TERMS OF VALUE - Elizabeth Juleny Tapotubun; Ismael Marasabessy (Berkala Perikanan Terubuk, 2022)
The Kei Islands are islands whose staple food is enbal. Enbal is a food that contains high carbohydrates, but other nutritional values are very low so efforts are needed to increase the nutritional content of enbal. The development of enbal which is a local food from the Kei Islands is a form of effort from regional subsidiaries to advance and introduce local food so that it is increasingly widely known. Various enbal preparations such as enbal sticks, enbal peanuts, enbal chocolate are early preparations that continue to progress along with the increasing public interest in consuming enbal. In addition to local food, huge marine resources such as fish, seaweed and shellfish are very abundant in the Kei Islands. The purpose  of this study is to determine the acceptability of panelists andproduce new products that have added value, and as a source of information to the public about processed enbal cripy shellfish mas ngur.  This activity consists of three stages. Phase I of the production of mas ngur shellfish, the second stage of plate enbal production and the third stage is the production of enbal krispy mas ngur. Based on the results of the activity, enbal crispy mas ngur is still accepted based on organoleptic assessments and is suitable for consumption and has a good appearance, aroma, taste, and texture and kerang mas ngur can be used as a fortification material rich in protein with an addition of 20%.